The Moral Philosophy of Sibhat Gebre-Egziabher in Selected Works: - - Feleke, Dessalegn Seyoum; Fikre, Ayele; Merawi, Fasil Merawi (Ethiopian Journal of Language, Culture and Communication, 2026)
Abstract This study rereads and reinterprets two works by Sibhat Gebre-Egziabher, namely Sebategnaw Meleak (The Seventh Angel) and Tikusat (Fever). The analytical approach employed in this study is grounded in concepts of moral philosophy. The justification for the notion of “rereading” lies in the fact that the study advances perspectives that have not been addressed by previous researchers. The absence of prior analyses that examine these works explicitly from the standpoint of moral philosophy constitutes the principal motivation for undertaking this research. The study adopts a qualitative research method, with particular emphasis on the examination and interpretation of moral discourse (morality). It analyzes the moral dilemmas raised in Sebategnaw Meleak and Tikusat, as well as the strategies employed to confront and resolve these dilemmas, using the conceptual framework of Ethical Egoism. The findings indicate that the novels function as vehicles for the author’s moral philosophy and confirm that Sibhat Gebre-Egziabher’s ethical outlook is fundamentally grounded in self-interest, that is, Ethical Egoism. Sebategnaw Meleak and Tikusat are novels in which social interests are marginalized, human moral virtue is neglected, moral obligations are dismissed, and universal moral good is rendered insignificant. The analysis establishes that egoistic moral reasoning predominates in the ethical vision articulated in the selected works.